A Draft Transcriptome Announcement of Anguina tritici - Kumar Manish; Neeraj; Hada Alkesh; Somvanshi Vishal Singh; Singh Ashish Kumar; Yadava Yashwant Kumar; Jain Pradeep Kumar; Gaikwad Kishore; Sirohi Anil (Journal of Nematology)
Anguina tritici, the wheat seed gall nematode, causes the ‘ear-cockle’ or seed gall disease of wheat (Triticum sp.), leading to an extensive decline of yield (30–70%) in underdeveloped wheat cultivating countries of the world. The nematode is known to survive in anhydrobiotic conditions for up to 32 years. Here, we present the first transcriptome assembly of A. tritici, which will be a valuable resource for understanding the genes responsible for nematode survival and above-ground plant parasitism. The final 133.2 Mb assembly consists of 105606 open reading frames (including isoforms) with the following BUSCO scores against Nematoda database: 80.3% complete (16.4% single copy and 63.9% duplicated), 2.1% fragmented, and 17.6% missing.